2008
DOI: 10.1294/jes.19.91
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Human Interferon-alpha on Shipping Fever of Thoroughbred Racehorses

Abstract: To assess the effect of human interferon-alpha (IFNα) on shipping fever of Thoroughbred racehorses subjected to long-distance transportation, an IFNα preparation was orally administered to 48 horses three times (once daily, 3 successive days) before transportation (IFNα group). In the control group (25 horses), maltose was administered in the same way. These treatments induced no abnormal findings in Thoroughbred racehorses before transportation. Immediately after transportation, significant increases in recta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 13 publications
(23 reference statements)
0
14
0
1
Order By: Relevance
“…A previous study tested the efficacy of IFN-α administration before transportation of racehorses [ 1 ]. That study showed that although IFN-α did not decrease the incidence of fever associated with transportation, IFN-α significantly reduced inflammation and improved the clinical conditions of horses compared with those of control horses [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous study tested the efficacy of IFN-α administration before transportation of racehorses [ 1 ]. That study showed that although IFN-α did not decrease the incidence of fever associated with transportation, IFN-α significantly reduced inflammation and improved the clinical conditions of horses compared with those of control horses [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study tested the efficacy of IFN-α administration before transportation of racehorses [ 1 ]. That study showed that although IFN-α did not decrease the incidence of fever associated with transportation, IFN-α significantly reduced inflammation and improved the clinical conditions of horses compared with those of control horses [ 1 ]. In the present study, we prophylactically treated all the test horses with IFN-α at a dose similar to that used in the previous report [ 1 ], but we found significant differences in the numbers of horses with fever and in the results of the hematologic analysis after transportation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Захисна дія людського інтерферону була продемонстро-вана у культурах клітин різних видів тварин: Пероральне уведення людського ре-комбінантного інтерферону коням суттєво по-кращувало стан тварин при запалювальних за-хворюваннях дихальних шляхів [78], а також зменшувало прояви лихоманки, спричиненої стресом перевезення, і покращувало стан тва-рин [3]. Рекомбінантний інтерферон-альфа (людський і тваринний), який вводили інтра-назально, захищав хутрових звірів (фреток) від сезонних проявів вірусу грипу [60].…”
Section: The Information About the Use Of Interferons In Veterinary Munclassified